Student Perceptions and Responses: Learning Using E-Module Physics-Math II - Astalini Astalini; Darmaji Darmaji; Dwi Agus Kurniawan; Siti Rohana (STKIP Singkawang, 2023)
Perception is influenced by several factors, one of which is biological factors such as gender. Gender is closely related to how different decisions are made between women and men. Based on the results obtained, it can be concluded that there are differences in the level of perception for each class which has two different genders, namely female and male. From the Anova table, it is found that the significance is smaller than 0.05 which indicates that both men and women have an average difference in perception about the product in the form of an e-module of Physics-Mathematics with double integral material.